Fatherless dan Peer Pressure pada Remaja di Jakarta - Zahry, Chanakya Diefta; Nuraqmarina, Fatma; Afrilya, Zeni (Merpsy Journal, 2025)
Abstract: This study aims to examine the relationship between fatherlessness and peer pressure among adolescents in Jakarta. The method used is a design bivariat with a quantitative approach. The sampling technique employed is non-probability sampling of the accidental type, with a total of 384 respondents drawn from the population of adolescents in Jakarta. The instruments used include the Peer pressure Inventory (Clasen & Brown, 1985) and the Father Presence Questionnaire (Krampe & Newton, 2006). The results of the study indicate a significant positive relationship between fatherlessness and peer pressure. This finding suggests that the higher the level of fatherlessness experienced by adolescents, the greater the peer pressure they perceive. In other words, the more absent a father is in an adolescent's life, the stronger the peer pressure they feel, which may lead to behaviors they find undesirable or uncomfortable. This study highlights the importance of a father's presence in supporting the emotional and social development of adolescents and in mitigating the negative impact of peer pressure.